An Optimization-based Tool to Support the cost-effective Production of Software Architecture Documentation - Nicoletti, Matías (2016)
We present a tool approach that aims at (i) assisting the documentation writer in their tasks and (ii) ensuring a cost-effective documentation process by means of optimization techniques. Our tool, called SADHelper, follows the principle of producing reader-oriented doc-umentation, in order to focus the available, and often limited, resources on gen-erating just enough documentation that satisfies the stakeholders' concerns.